2014
DOI: 10.1007/s00049-014-0169-y
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl disulfide and dimethyl trisulfide: so similar yet so different in evoking biological responses in saprophilous flies

Abstract: Dimethyl disulfide (DMDS) and dimethyl trisulfide (DMTS) are used by saprophilous insects to locate breeding sites (decaying organic matter), and by brood-site deceptive flowers to attract such insects. However, little is known about the relative importance of these two compounds in eliciting electrophysiological and behavioural responses in the insects. Here, we compared the relative attractiveness of DMDS and DMTS to saprophilous flies in field choice experiments and tested whether potential differences in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 17 publications
6
35
0
Order By: Relevance
“…Even if DMTS elicited the strongest physiological response, it did not play any role in the attraction of house flies. A similar result recently has been shown by Zito et al (2014). This compound, therefore, seems generally not to elicit attractive responses in house flies despite being sensitively detected by their antennae.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Even if DMTS elicited the strongest physiological response, it did not play any role in the attraction of house flies. A similar result recently has been shown by Zito et al (2014). This compound, therefore, seems generally not to elicit attractive responses in house flies despite being sensitively detected by their antennae.…”
Section: Discussionsupporting
confidence: 84%
“…This compound, therefore, seems generally not to elicit attractive responses in house flies despite being sensitively detected by their antennae. In other flies (Calliphoridae), however, this compound does elicit both antennal and positive behavioral responses (Zito et al 2014). In behavioral assays, Cossé and Baker (1996) showed that mixtures are better attractants for house flies looking for breeding sites than single compounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15). 40,66a The homology model was felt to be appropriate because of the high sequence identity between the MOR244-3 and M2 receptor TM regions. A common structural feature of both MOR244-3 and the M2 receptor is an internal aqueous channel (Fig.…”
Section: Demonstration Of the Activation Of Olfactory Receptors By mentioning
confidence: 99%